Prevention and Recovery Care Services in Australia: Describing the Role and Function of Sub-Acute Recovery-Based Residential Mental Health Services in Victoria - Fletcher, Justine; Brophy, Lisa; Killaspy, Helen; Ennals, Priscilla; Hamilton, Bridget; Collister, Laura; Hall, Teresa; Harvey, Carol (Frontiers in Psychiatry, 2019)
Background: Prevention and Recovery Care (PARC) services are relatively new sub-acute residential services that have supported people with mental ill-health in Victoria since 2003. Operated from a partnership model between non-governmental agencies and clinical mental health services, PARC services integrate intensive recovery-focused psychosocial input with clinical mental health care. Aim: To describe and contrast the 19 PARC services operating in Victoria at the time of the study, in terms of structures and function, resources, and content and quality of care. Method: Nineteen participants, one representing each PARC, completed two surveys: the first, a purpose-designed survey relating to the government guidelines for PARC services, and the second, the Quality Indicator for Rehabilitative Care. Results: Descriptive analyses highlighted that PARC services have operated in inner-city, urban, and regional areas of Victoria, from between 1 and 14 years. Participants reported that a recovery approach was at the core of service delivery, with a vast array of group and individual programs on offer. Across the state, there was variation in the quality of services according to the Quality Indicator for Rehabilitative Care domains. Conclusions: This study has identified that there is variation in the structure and function, resourcing, and content and quality of care offered across Victoria’s PARC services even though, in the main, they are guided by government guidelines. Hence it appears that the services adapt to local needs and changes in service systems occurring over time. The findings indicate emerging evidence that PARCs are providing recovery-oriented services, which offer consumers autonomy and social inclusion, and therefore likely enable a positive consumer experience. The range of individual and group programs is in line with the Victorian guidelines, offering practical assistance, therapeutic activities, and socialization opportunities consistent with consumer preferences. Further research into implementation processes and their impacts on quality of care is warranted concerning this and similar service models.